2019
DOI: 10.1186/s13071-019-3551-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Hepatozoon felis in cats from Maio Island, Republic of Cape Verde and global distribution of feline hepatozoonosis

Abstract: Background Vector-borne diseases are emerging worldwide and have an important zoonotic relevance. In the last few years, the interest in vector-borne pathogens in cats has increased. However, studies on feline vector-borne pathogens on tropical islands are lacking. Islands differ from continental countries because they have an enclosed population of animals, with all year presence of the vectors and, most often, without vector control measures. This study focused on the molecular identification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 69 publications
(89 reference statements)
2
14
0
2
Order By: Relevance
“…Several recent screening approaches have shone light on the genetic diversity within H. felis in mammals in Africa. Pereira et al ( 2019 ) identified H. felis in 15% of cats from Maio Island, in the Cape Verde archipelago, all of which were identical to a haplotype previously identified in cats from Spain. Hepatozoon felis from cats in Angola (Oliveira et al 2018 ) also shared this and two other closely related haplotypes (47, 49 and 51, Figure 1 ).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Several recent screening approaches have shone light on the genetic diversity within H. felis in mammals in Africa. Pereira et al ( 2019 ) identified H. felis in 15% of cats from Maio Island, in the Cape Verde archipelago, all of which were identical to a haplotype previously identified in cats from Spain. Hepatozoon felis from cats in Angola (Oliveira et al 2018 ) also shared this and two other closely related haplotypes (47, 49 and 51, Figure 1 ).…”
Section: Discussionmentioning
confidence: 60%
“…Common companion animals such as dogs and cats play a key role in the epidemiology of various pathogens, acting as both reservoirs and sentinels. Surprisingly therefore, studies of feline vector-borne infections are less prevalent than those of canine vector-borne infections (Pereira et al 2019 ). This is despite the fact that cats often spend considerable time outdoors, in areas with high risk of exposure to ticks and other vectors (Persichetti et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В острый период, кроме лихорадки и признаков интоксикации регистрируется лейкопения, тромбоцитопения, анемия, повышенные уровни аланинаминотрансферразы и креатинина (Limeira et al, 2019;Pusterla, Braun, Leutenegger, Reusch, & Lutz, 2000). Клинически у таких животных отмечается субиктеричность и иктеричность склер, на фоне лихорадки у таких животных часто диагностируют бабезиоз, кроме эрлихиоза, что требует дифференциальной диагностики (Hegarty et al, 2015;Malheiros et al, 2016;Pereira et al, 2019).…”
unclassified
“…Отмечено рядом авторов, что касается диагностики заболевания, что только прямая микроскопия мазка периферической крови дает возможность выявить возбудителя на ранней стадии заболевания при поражении 4 % моноцитов (Nalubamba et al, 2015;Halac, 2016;Pereira et al, 2019;Qin et al, 2019;Peterson, 2000). Диагностика с помощью молекулярного анализа (секвенирование, полимеризация ДНК в ПЦР) позволила обнаружить 8 различных генов эрлихий и установить возможность диагностики эрлихиозов животных с использованием праймеров ДНК (Cardoso, Tuna, Vieira, Yisaschar-Mekuzas, & Baneth, 2010;Attipa et al, 2017…”
unclassified